Methyljasmonate accelerates catabolism of monoterpenoid indole alkaloids in Catharanthus roseus during leaf processing - El-Sayed, M.; Verpoorte, R.
Variations in alkaloid pattern during drying of leaves (leaf processing)showed that treatment with methyljasmonate can induce formation of bisindole alkaloids as a result of catabolism of the monomeric alkaloids catharanthine and vindoline. A twofold increase in 3',4'-anhydrovinblastine was shown in treated leaves especially from day 8 until day 21. Serpentine also increased in the same period under the treatment as a catabolic product of ajmalicine. Basic peroxidases that are responsible for the formation of anhydrovinblastine and serpentine showed high activity at days 8 and 21 in treated leaves, causing the increase in anhydrovinblastine and serpentine.
Keywords: CATHARANTHUS ROSEUS; ALKALOID CATABOLISM; DRYING PROCESS; JASMONATE; PEROXIDASES